Bacterial Population Dynamics of Natural Fermentation of Sumbawa Mare’s Milk Using Metagenomic Approach - Yoga Dwi Jatmiko; Aditya Ragil Suharto; Irfan Mustafa; Siska Aditya (Indonesian Society for microbiology, 2021)
This study aimed to assess the changing of bacterial density and the physicochemical aspects during natural fermentation of Sumbawa mare’s milk, and to evaluate the dynamics of bacterial population during the natural fermentation using metagenomic approach. Mare’s milk sample obtained from Regency of Dompu were fermented for 60 days. On the day 0, 7, 15, 30 and 60 mare milk sample were collected for further analysis, such as bacterial density enumeration, nutrition content, physical properties of the milk, and total DNA isolation. The total DNA samples obtained were analyzed using next generation sequencing. The density of lactic acid bacteria was decreased along with fermentation periods. Meanwhile, the density of aerobic bacteria on was relatively fluctuated. The physicochemical content of mare’s milk also changed during fermentation periods. Carbohydrate content and total sugar was decrease along with the decreasing of pH value. Moreover, the lipid content increase, and the protein content was fluctuated. The changing in physical properties such as whey color, acidity and gas was observed until the end of mare’s milk natural fermentation process. Using metagenomics analysis, the bacterial diversity from each sample periods categorized as low because of the dominance of Lactobacillus helveticus until the end of the fermentation. Lactobacillus helveticus as a member of LAB did not grow on isolation media on the late stage of fermentation periods (day-60). The presence of uncultivable bacteria can be detected with metagenomic approach, fulfilling the limited information on the bacterial composition of fermented Sumbawa mare’s milk products.